P. KULISH'S CREATIVITY IN THE LITERARY CRITIC'S RECEPTION BY YU. LAVRINENKO - Лущій, С. (Київський національний університет імені Тараса Шевченка, 2020)
The article considers the reception of P. Kulish's works in Yuri Lavrinenko's literary works, in particular in the texts of radio broadcasts made on radio "Svoboda". The subject of the study were the literary-critical articles and correspondence. The study involves the use of unknown archival sources. The article deals with the letters and radio broadcasts be Jurii Lavrinenko kept in the Department of Manuscripts and Textual Studies of Shevchenko Institute of Literature of the National Academy of Sciences of Ukraine. The article explains the reasons for the researcher's interest in this figure. Yuri Lavrinenko sought to find the traditions of P. Kulish not only in the works of the writers of the "Executed Renaissance", the "Prague School", but also in the younger generation of writers of the Diaspora. The purpose of the radio talks about P. Kulish is to interest the readers of the creativity of this classic, especially his historical novel "Сhorna rada". In radio broadcasts Yu. Lavrinenko draws attention to the artistic, historical and philosophical views of P. Kulish. The literary critic became a popularizer of P. Kulish's work in the Diaspora.

Розглянуто рецепцію творчості П. Куліша в літературознавчих працях Ю. Лавріненка, зокрема передачах, виголошених на радіо "Свобода". Подано ті листи та радіопередачі Ю. Лавріненка, які зберігаються у відділі рукописних фондів і текстології Інституту літератури ім. Т. Г. Шевченка НАН України. З'ясовано причини зацікавлення дослідника цією постаттю. Ю. Лавріненко прагнув віднайти традиції П. Куліша не лише у творах письменників "розстріляного відродження", "Празької школи", й у молодшого покоління письменників діаспори.
ТВОРЧІСТЬ П. КУЛІША В ЛІТЕРАТУРОЗНАВЧІЙ РЕЦЕПЦІЇ Ю. ЛАВРІНЕНКА
Keywords: P. Kulish; Yu. Lavrinenko; reception; radio broadcasts; Diaspora; рецепція; радіопередачі; листи; діаспора; критик